2017
DOI: 10.1590/s1980-6574201700010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise training on cGMP levels and blood pressure in treated hypertensive postmenopausal women

Abstract: -The second messenger cGMP has been largely studied as a therapeutic target in a variety of disorders such as erectile dysfunction, arterial hypertension and heart failure. Evidence has shown that cGMP activators are less efficient in estrogen-deficiency animals, but no studies exist involving non-pharmacological approaches on NO/ cGMP signaling pathway in hypertensive postmenopausal women. The aim of this study is to examine NO/cGMP pathway, redox state and blood pressure in trained treated hypertensive (HT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…This category consists of seven publications [10][11][12][13][14][15][16] that address the effects of exercise on the metabolism of menopausal women. The authors mainly focused on the endocrine metabolism and the normalization of the body's hormones in order to improve the well-being of women under these conditions.…”
Section: The Influence Of Physical Exercise On the Metabolism Of Postmentioning
confidence: 99%
See 2 more Smart Citations
“…This category consists of seven publications [10][11][12][13][14][15][16] that address the effects of exercise on the metabolism of menopausal women. The authors mainly focused on the endocrine metabolism and the normalization of the body's hormones in order to improve the well-being of women under these conditions.…”
Section: The Influence Of Physical Exercise On the Metabolism Of Postmentioning
confidence: 99%
“…Of the articles analyzed, four [10][11][12][13] addressed the contributions of physical exercise to the lipid metabolism, the reduction of waist circumference and weight loss. One study 11 demonstrated that regular exercise training over a three-month period resulted in a significant improvement in metabolic parameters, with a significant increase in HDL level, a significant reduction in LDL level, improved physical fitness and heart rate and diastolic blood pressure normalization, reducing cardiovascular risks over ten years when analyzed by the Framingham scale 10,11 . In addition, the studies 14,15 highlighted that performing exercise as a non-pharmacological intervention is a valuable therapeutic resource in postmenopausal women, acting positively in reducing visceral adipose tissue, waist circumference and BMI. It also promotes greater respiratory capacity, ensuring greater functional capacity and quality of life among these women.…”
Section: The Influence Of Physical Exercise On the Metabolism Of Postmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies report that eight weeks of aerobic physical exercise reduce systolic BP, diastolic BP, and heart rate in hypertensive postmenopausal women approximately −3.8%, −5.9%, and −3.9%, respectively [ 22 ]. Aerobic or resistance exercise is known to effectively reduce blood pressure, which is associated with the improved cardiovascular autonomic mechanisms in hypertensive postmenopausal state [ 15 , 29 , 30 ]. A previous study reported that eight weeks of low-to-moderate- intensity exercise (50–60% maximal running speed) can enhance cardio-metabolic benefits, which are related to reduced blood pressure and autonomic dysfunction in hypertensive rats submitted to ovarian hormone deprivation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Is there an endothelial dysfunction after menopause? Previous studies have systematically shown that NO/cGMP signaling pathway, as well as flow-mediated dilation, is not impaired in hypertensive postmenopausal women as compared with normotensive subjects (Sponton et al, 2014;Puga et al, 2016;Jarrete et al, 2016;Novais et al, 2017). Additionally, both hypertensive and normotensive postmenopausal women were responsive to aerobic exercise training (AET) by increasing the endothelial biomarkers related to NO/cGMP pathway (Sponton et al, 2010;Rezende et al, 2011).…”
mentioning
confidence: 99%